PENGARUH PROMOSI MELALUI MEDIA SOSIAL DAN ELECTRONIC WORD OF MOUTH TERHADAP LOYALITAS PELANGGAN ASIAN BOWL SURABAYA - Kevin Owen Wibisono; Hendro Susanto (Jurnal Performa)
The purpose of this research is to analyze the influence of promotion through social media and eWOM on customer loyalty of Asian Bowl Surabaya. Asian Bowl Surabaya is a food business that sells chicken katsu as its main menu. In this research, it is observed how customer loyalty on Asian Bowl can be formed or influenced by promotion and electronic word of mouth. This research data is obtained from questionnaire distribution to respondents of 121. That data is processed by using multiple linear regression method. The result of the research shows that promotion variabel affects significant on customer loyalty, eWoM variabel also affects significant on customer loyalty.